THE INFLUENCE OF FINANCIAL KNOWLEDGE ON ONLINE SHOPPING BEHAVIOR OF SURABAYA STUDENTS - Putri, Aulita Safitri Arminda; Sari, Lian Alvionita (Jurnal Pijar, 2024)
This study aims to analyze the influence of financial knowledge on Surabaya students' online shopping behavior. A quantitative approach with a descriptive survey was used, involving a population of active university students in Surabaya who use online shopping platforms. A sample of 105 students was selected through purposive sampling. Data was collected using questionnaires distributed through Google Forms and social media, covering demographics, financial knowledge, and online shopping behavior. Data analysis used descriptive statistics and simple linear regression with SPSS. Results showed a significant positive influence of financial knowledge on more planned and rational online shopping behavior. The correlation coefficient of 0.623 indicates a strong relationship between the two variables. The implication is that increasing financial literacy can encourage wiser consumer behavior among university students. This study highlights the importance of financial education in shaping more controlled spending habits, allowing individuals to differentiate between primary and secondary needs. Further studies are recommended to reach a wider range of respondents geographically and demographically